2019
DOI: 10.1111/ijcp.13380
|View full text |Cite
|
Sign up to set email alerts
|

Serum CA‐125 levels in preeclampsia: A systematic review and meta‐analysis

Abstract: Background Preeclampsia is a leading cause of perinatal morbidity, although an optimal screening model is still under investigation. The aim of the present meta‐analysis is to accumulate current evidence and evaluate the diagnostic accuracy of CA‐125 in preeclampsia. Materials and Methods Medline, Scopus, CENTRAL, Clinicaltrials.gov and Google Scholar were systematically searched. All studies reporting serum CA‐125 among preeclamptic and healthy pregnant women were selected. Results Nine studies involving 977 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…4. The elevation of CA-125 in PE patients in this study agreed with many previous studies [21,23,28,44], in which some authors suggesting that CA125 is a promising biochemical marker, and can reflect the severity of preeclampsia [7,11,18,21,23,28,43,[45][46][47]. "This rising level of CA-125, might be due to failure of trophoblastic invasion, and the induction of an inflammatory process within placenta, that triggers the expression of CA-125.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…4. The elevation of CA-125 in PE patients in this study agreed with many previous studies [21,23,28,44], in which some authors suggesting that CA125 is a promising biochemical marker, and can reflect the severity of preeclampsia [7,11,18,21,23,28,43,[45][46][47]. "This rising level of CA-125, might be due to failure of trophoblastic invasion, and the induction of an inflammatory process within placenta, that triggers the expression of CA-125.…”
Section: Discussionsupporting
confidence: 93%
“…There are few clinical studies related to the use of CA-125 in hypertensive disorders of pregnancy with conflicting results" [20]. "However, some studies reported positive correlation between serum CA125 concentration and preeclampsia" [21][22][23][24]. "C -reactive protein (CRP) is an acute phase protein produced by hepatocyte in response to release of Pro-inflammatory cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…comparison with the control group (p<0.001) which was observed in the current study, coinciding with many previous studies [21,23,28] in which some authors suggested that CA-125 is a promising biochemical marker and can reflect the severity of preeclampsia [18,21,23,28,41]. This rise might be due to failure in trophoblastic invasion and the induction of an inflammatory process within the placenta that triggers the expression of CA-125 and is anticipated to be an essential mechanism for the elevation of serum CA-125 in preeclampsia.…”
Section: Plos Onesupporting
confidence: 93%
“…There are few clinical studies related to the use of CA-125 in hypertensive disorders of pregnancy with conflicting results [20]. However, some studies reported positive correlations between serum CA-125 concentration and preeclampsia [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that cancer antigen (CA) 125 values increase during pregnancy and in cases of preeclampsia [12]. Considering that HE4 has been associated with many diseases, such as cancer and endometriosis, diseases that are also associated with increased CA 125 levels, it is necessary to investigate the relationship between preeclampsia and HE4 [6][7][8].…”
Section: Introductionmentioning
confidence: 99%